Religion and resistance in Appalachia : faith and the fight against mountaintop removal coal mining - Witt, Joseph D. (Place Matters: New Directions in Appalachian Studies., 2016)
In the last fifty years, the Appalachian Mountains have suffered permanent and profound change due to the expansion of surface coal mining. The irrevocable devastation caused by this practice has forced local citizens to redefine their identities, their connections to global economic forces, their pasts, and their futures. Religion is a key factor in the fierce debate over mountaintop removal; some argue that it violates a divine mandate to protect the earth, while others contend that coal mining is a God-given gift to ensure human prosperity and comfort. In Religion and Resistance in Appalachia: Faith and the Fight against Mountaintop Removal Coal Mining, Joseph D. Witt examines how religious and environmental ethics foster resistance to mountaintop removal coal mining. Drawing on extensive interviews with activists, teachers, preachers, and community leaders, Witt's research offers a fresh analysis of an important and dynamic topic. His study reflects a diversity of denominational perspectives, exploring Catholic and mainline Protestant views of social and environmental justice, evangelical Christian readings of biblical ethics, and Native and nontraditional spiritual traditions. By placing Appalachian resistance to mountaintop removal in a comparative international context, Witt's work also provides new outlooks on the future of the region and its inhabitants. His timely study enhances, challenges, and advances conversations not only about the region, but also about the relationship between religion and environmental activism.